The Protective Effects of Alisol A 24-Acetate from Alisma canaliculatum on Ovariectomy Induced Bone Loss in Vivo - Hwang, Yun-Ho (Molecules, 2016)
Alisma canaliculatum is a herb commonly used in traditional Korean medicine, and has been shown in scientific studies to have antitumor, diuretic hepatoprotective, and antibacterial effects. Recently, the anti-osteoclastogenesis of alisol A 24-acetate from Alisma canaliculatum was investigated in vitro. However, the influence of alisol A 24-acetate on osteoporosis in animals has not been investigated. The present study was undertaken to investigate the anti-osteoporotic effect of alisol A 24-acetate on bone mass in ovariectomized (OVX) mice and to identify the mechanism responsible for its effects. OVX mice were treated daily with 0.5 or 2 μg/g of alisol A 24-acetate for a period of six weeks. It was found that these administrations significantly suppressed osteoporosis in OVX mice and improved bone morphometric parameters. The serum estradiol, bone alkaline phosphatase levels, regulatory T/Th17 cell numbers were significantly increased by alisol A 24-acetate as compared with untreated OVX mice. In addition, TRAP activity was inhibited by alisol A 24-acetate in OVX mice. These results suggest alisol A 24-acetate effectively prevents bone loss in OVX mice, and that it can be considered a potential therapeutic for the treatment of postmenopausal osteoporosis.